Combined uterorelaxant effect of magnesium sulfate and terbutaline: Studies on late pregnant rat uteri in vitro and in vivo. (19th February 2023) - Barna, Tamara; Szucs, Kalman F.; Schaffer, Annamaria; Mirdamadi, Mohsen; Hajagos‐Toth, Judit; Gaspar, Robert
Abstract: Introduction: Preterm delivery and its complications are among the biggest challenges and health risks in obstetrical practice. Several tocolytic agents are used in clinical practice, although the efficacy and side effect profiles of these drugs are not satisfying. The aim of this study was to investigate the uterus relaxant effect of the coadministration of β2 ‐mimetic terbutaline and magnesium sulfate (MgSO4 ) in an isolated organ bath and to perform in vivo smooth muscle electromyographic (SMEMG) studies in pregnant rats. In addition, we also investigated whether the tachycardia‐inducing effect of terbutaline can be reduced by the presence of magnesium, due to the opposite heart rate modifying effects of the two agents. Material and methods: In the isolated organ bath studies, rhythmic contractions of 22‐day‐ pregnant Sprague–Dawley rats were stimulated with KCl, and cumulative dose–response curves were constructed in the presence of MgSO4 or terbutaline. The uterus‐relaxing effects of terbutaline were also investigated in the presence of MgSO4 in both normal buffer and Ca 2+ ‐poor buffer. The in vivo SMEMG studies were carried out under anesthesia with the subcutaneous implantation of an electrode pair. The animals were treated with MgSO4 or terbutaline alone or in combination in a cumulative bolus injection. The implanted electrode pair also detected the heart rate. Results: Both MgSO4 and terbutaline reduced uterine contractions in vitro and in vivo, furthermore, the administration of a small dose of MgSO4 significantly enhanced the relaxant effect of terbutaline, especially in the lower range. However, in Ca 2+ ‐poor environment, MgSO4 was not able to increase the effect of terbutaline, indicating the role of MgSO4 as a Ca 2+ channel blocker. In the cardiovascular studies, MgSO4 significantly decreased the tachycardia‐inducing effect of terbutaline in late pregnant rats. Conclusions: The combined application of MgSO4 and terbutaline may have clinical significance in tocolysis, which must be confirmed in clinical trials. Furthermore, MgSO4 could substantially reduce the tachycardia‐inducing side effect of terbutaline. Abstract : MgSO4 significantly enhanced the uterorelaxant effect of terbutaline, while the tachycardia‐inducing adverse effect of terbutaline was reduced. The combined application of MgSO4 and terbutaline may have clinical significance in tocolysis.